Chronic adventitial inflammation, vasa vasorum expansion, and 5‐lipoxygenase up‐regulation in irradiated arteries from cancer survivors. Issue 11 (16th August 2016) - Halle, Martin; Christersdottir, Tinna; Bfäck, Magnus
ABSTRACT: Radiation‐induced cardiovascular disease is an emerging problem in a steadily increasing population of survivorsof cancer. However, the underlying biology is poorly described, and the late onset, which occurs several years after exposure, precludes adequate investigations in animal and cell culture models. We investigated the role of the 5‐lipoxygenase (5‐LO)/leukotriene pathway in radiation‐induced vascular changes. Use of paired samples of irradiated arteries and nonirradiated internal control arteries from the same patient that were harvested during surgery for cancer reconstruction £10 yr after radiotherapy provides a unique human model of chronic radiation–induced vascular changes. Immunohistochemical stainings and perioperative inspection revealed an adventitial inflammatory response, with vasa vasorum expansion and chronic infiltration of CD68 + macrophages. These macrophages stained positive for the leukotriene‐forming enzyme 5‐LO. Messenger RNA levels of 5‐LO and leukotriene B4 receptor 1 were increased in irradiated arterial segments compared with control vessels. These results point to targeting the 5‐LO/leukotriene pathway as a therapeutic adjunct to prevent late adversevascular effects of radiotherapy.—Halle, M., Christersdottir, T., Bäck, M. Chronic adventitial inflammation, vasa vasorum expansion, and 5‐lipoxygenase up‐regulation in irradiated arteries from cancer survivors. FASEB J. 30, 3845–3852 (2016) www.fasebj.org